The effect of outage duration and outage frequency on customer satisfaction of PT PLN (persero) ULP Simpang Empat - Yass Andria; Jondri Yoza; Yoserizal Yoserizal; Sonya Futri Ramafina (Institute of Computer Science (IOCS), 2023)
This research is motivated that customer satisfaction is part of one of PLN's missions, namely running the electricity business and other related fields, oriented to customer satisfaction, company members and shareholders. Customer satisfaction in the PLN ULP Simpang Empat area is the outermost unit of PLN West Sumatra needs to be measured to be a reference to the extent of the effectiveness of the budget spent by PLN to achieve the target of outage duration (SAIDI) and outage frequency (SAIFI) This study aims to determine the effect of 1) Outage Duration on Customer Satisfaction, 2) Outage Frequency on Customer Satisfaction. This type of research uses a quantitative approach with multiple linear regression methods. Data collection techniques with questionnaires. The respondents of this study were 100 PLN customers in the PLN ULP Simpang Empat work area. The sampling method uses the Proportional Stratified Random Sampling method. Hypothesis testing is calculated with the SmartPLS 3.0 program. From the results of this study it was found that: 1) The duration of the outage has a positive and significant influence on customer satisfaction. 2) The frequency of outages has a positive and significant influence on customer satisfaction.